Analysis of Intuitive and Analytics Thinking Processes in Middle School Students in Solving National Mathematics Exam - Safrina, Khusnul (Al-Khawarizmi, 2021)
So far, the teacher's thought process in solving a math problem has rarely been paid attention to by the teacher. The thinking process of students in solving math problems includes intuitive and analytical thinking processes. The aim of this research is to explore the intuitive and analytical thinking process of junior high school students in solving UN questions. The research method used is qualitative research that is exploratory in nature by selecting subjects who have high abilities in mathematics. Data collection in the form of descriptions of students' intuitive and analytical thinking processes was carried out through interviews. The results obtained in this study are a description of the process that students go through in mental when students solve math problems in the form of questions National Examination. The results of the study can be concluded that students in solving mathematics problems in the National Examination prioritize the process of intuitive thinking, where students can spontaneously and directly pour out ideas for solving the problems given. In addition, in the further process, students also use analytical methods. Analytical thinking processes are carried out by students by detailing the answers based on the information in the questions.